PERAN ETIKA KERJA ISLAMI DAN KNOWLEDGE SHARING DALAM MENINGKATKAN KAPABILITAS INOVASI PADA RUMAH SAKIT UMUM BAHTERAMAS PROVINSI SULAWESI TENGGARA - Busra Busra (Jurnal Riset Bisnis Indonesia, 2014)
The purpose of this study to investigate the influence of Islamic work ethics, organizational cultureand knowledge sharing on innovation capability nurse at Bahteramas Public Hospital SoutheastSulawesi Province. A total of 75 nurses were respondents with proportional purposive samplingtechnique spread to all unit of nursing service. The analytical tool is used structural equation modelingwith alternative methods Partial Least Square (PLS).The results showed that: (1) Islamic work ethicsignificantly brings positive impact on innovation capability, (2) Islamic work ethic significantly bringspositive impact on knowledge sharing, (3) There is no significant and positive impact betweenorganizational culture and innovation capability, (4) Organizational culture significantly brings positiveeffect on knowledge sharing, (5) Knowledge sharing significantly brings positive impact on innovationcapability.Keywords: Islamic work ethics, organizational culture, knowledge sharing and innovation capability.